2022
DOI: 10.1021/acsestwater.1c00453
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Emerging Contaminants in Southeast Asian Environments: Present Status, Challenges, and Future Prospects

Abstract: The status of emerging contaminant (EC) profiles in Southeast Asia is currently unclear and often overshadowed by studies conducted in developed regions such as North America, Europe, and Asia. EC research in Southeast Asia is especially critical due to its high population density and poor sanitation infrastructure that introduce large amounts of ECs into the aquatic environment. This literature Review investigated the status of EC research in 11 Southeast Asian countries. Key pharmaceutical groups such as ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 181 publications
0
15
0
Order By: Relevance
“…In a recent review of the journal articles on emerging contaminants in SEA revealed that pesticides were second to pharmaceutical compounds. Among the pesticides, atrazine, glyphosate and paraquat have been identified as emerging contaminants, with atrazine concentrations being reported as way below the standards (Lee et al, 2022). Meanwhile, atrazine and 2,4-D were detected in surface and groundwater samples in Thailand indicating groundwater contamination (Laohaudomchok et al, 2021).…”
Section: 3 Environmental Impacts Of Herbicide Usementioning
confidence: 99%
“…In a recent review of the journal articles on emerging contaminants in SEA revealed that pesticides were second to pharmaceutical compounds. Among the pesticides, atrazine, glyphosate and paraquat have been identified as emerging contaminants, with atrazine concentrations being reported as way below the standards (Lee et al, 2022). Meanwhile, atrazine and 2,4-D were detected in surface and groundwater samples in Thailand indicating groundwater contamination (Laohaudomchok et al, 2021).…”
Section: 3 Environmental Impacts Of Herbicide Usementioning
confidence: 99%
“…Emerging contaminants have become a topic of growing interest in wastewater treatment. Antibiotics are just one of the key emerging contaminants that fall under the heading of pharmaceuticals [12] . The oxytetracycline (OTC), an antibiotic belonging to the tetracycline family, is among the most commonly prescribed and toxic antibiotics [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, millions of previous studies have been reported that, wastewater has been carrying a series of pollutants including emerging contaminants (ECs) [6][7][8][9][10]. The ECs including pharmaceuticals and personal care products (PPCPs) are presents in aquatic system of different locations of the world with higher concentration beyond permissible limit [11][12][13][14][15][16]. One of the pharmaceutical products, the antibiotics are using for killing of human and animal host pathogenic fungi and bacteria [5].…”
Section: Introductionmentioning
confidence: 99%